Rights of inmate mothers toward custody of children / Illi Marisqa Khalizan … [et al.] - Khalizan, Illi Marisqa; Mohmd, Nordiana; Zorkefrie, Nur Shakila; Abdul Ghani, Nur Wasilah (2011)
This project paper is focus on the rights of inmate mothers towards custody of the children. As there is lack of awareness among the society especially inmate mothers and the family members themselves, there is a need to look at this problem thoroughly. The aim of this project paper is to examine whether the current act and regulation namely Prison Regulation 2000 and Prison Act are sufficient in governing issue custody of children by inmate mother and to critically analyse the extent of the rights that available for the inmate mother towards custody of children. The main issue in this research is the regulation does not stipulate the rights of the inmate mother to be given choices to choose the custody of their children. Another issue is when the act that is the Prison Regulation 2000 is silent on the appropriate mechanism and person in charge of custody of children and inmate mothers Lastly the last issue that had been highlighted in this project paper is in the Prison Regulation 2000, the power of the Director General regarding children of female prisoners is not wide as they can only exercise several or limited powers. It is submitted that there is an urgent need to improvise the current act regarding matters of inmate mother. One way to do it is by amending the act to cover specifically on the rights of inmate mothers towards custody of children in order for the rights of inmate mothers to be protected.